Forgiveness as a Moderator between Perceived Unfair Treatment and Anger With own Children - Claudia Maria Dumondor; Susana Tjipto (Faculty of Psychology, Universitas Gadjah Mada, 2023)
Referring to Komisi Perlindungan Anak Indonesia (KPAI), the highest perpetrators in family violence were mothers (22%), but there has not been much research on the violence transmission from parents to children and the role of forgiveness as a protective factor. This study aims to examine the role of forgiveness as a moderator of the relationship between the perceived unfair treatment by family members of origin and anger with their own children. Participants involved in this study were 63 mothers who perceived unfair treatment by family members of origin and had children aged between 2 to 7 years old. Data were collected using 3 scales: Personal Forgiveness Scale, Family of Origin Hurt Scale, and Attitude toward Child Scale. The multiple regression analysis showed that there was a significant positive relationship between the perceived unfair treatment and anger with one's own child (gender similarity transmission sample, r = .75, p = .000,n = 31; all sample, r = .77, p = .000, n = 63). The analysis for gender similarity transmission sample showed that 56.7% (and for all samples, 58.4) of the variance in anger with one's own child was explained by the perceived unfair treatment by the mother. Meanwhile, forgiveness does not play as a moderator variable in the association of both variables. The implications of the results of this study are discussed.